How (Not) to Think of Emotions as Evaluative Attitudes. (7th November 2017) - Müller, Jean Moritz
Abstract: It is popular to hold that emotions are evaluative. On the standard account, the evaluative character of emotion is understood in epistemic terms: emotions apprehend or make us aware of value properties. As this account is commonly elaborated, emotions are experiences with evaluative intentional content. In this paper, I am concerned with a recent alternative proposal on how emotions afford awareness of value. This proposal does not ascribe evaluative content to emotions, but instead conceives of them as evaluative at the level of intentional mode or attitude (Deonna and Teroni2012, 2014, 2015 ). I first argue that this proposal fails to make emotions intelligible as value apprehensions. There are reasons to suppose that emotions do not apprehend value to begin with, but are related to values in a different, non‐epistemic sense. I then go on to show that the notion of an evaluative intentional mode can still help elucidate the evaluative character of emotion. I argue that there is a plausible non‐epistemic understanding of the view that emotions are evaluative modes. On this account, emotions are not ways of apprehending values, but ways of acknowledging values.